Variations of soymilk components during fermentation by Lactobacillus and Bifidobacterium strains - Elghali, Salma; Mustafa, Shuhaimi; Amid, Mehrnoush; Abd Manap, Mohd Yazid; Ismail, Amin; Abas, Faridah (WFL Publisher, 2014)
Bifidobacterium breve 15700, Bifidobacterium infantis 15697, Bifidobacterium longum BB536, Bifidobacterium pseudocatenulatum G4, Lactobacillus casei 01 and Lactobacillus plantarum FTCC 0350 were used to study the changes on soymilk components during fermentation. L. casei 01 and B. breve offered highly significant decrease (P < 0.05) in stachyose at 98.2 and 97.7%, respectively compared to L. plantarum (91.1%). Raffinosedecreased by 99.2 and 98.7% when soymilk was fermented with B. breve and B. pseudocatenulatum G4, respectively and was not detected with B. longum BB536, B. infantis, L. casei, and L. plantarum. Sucrose was significantly (p < 0.05) reduced by L. casei (97.5%) and B. infantis (80.7%). Onthe other hand, besides the reduction in the content of stachyose, raffinose, and sucrose, an increase in the levels of monosaccharides principally glucose, galactose, and fructose was observed. The percentage of increase in glucose level ranged between 72.75% to 85.415%, and the percentage of increase in galactose and fructose levels ranged between 54.70% to 78.54% and 65.44% to 84.05%, respectively. Acetic acid was produced highest by B. breve (6.8 mmol l-1) whereas lactic acid was highest in L. casei (10.7 mmol l-1) fermentation. It was found that, the metabolism of oligosaccharides, disaccharide and monosaccharides lead to the formation of short chain fatty acids (lactic acid and acetic acid) as by-products. The highest amount of acetic acid was produced by B. breve (6.80 mmol l-1). On the other hand, the highest amount of lactic acid was found in soymilk fermented with L. casei (10.70 mmol l-1).